2021
DOI: 10.5650/jos.ess21124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of δ-Tocopherol on Mice Adipose Tissues and Mice Adipocytes Induced Inflammation

Abstract: IntroductionIn Japan, one of three adult men is obese, which has been a long-term social problem. Obesity describes a condition in which an individual has not only overweight but also excessive body fat. It has been shown previously that monocyte chemoattractant protein-1 MCP-1 gene expression increases in enlarged mesentery adipose tissue with long-term obesity, which is followed by macrophage infiltration and activation 1 . Furthermore, inflammatory factors are produced form excessive infiltration of macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In this study, the ingestion of α-toc and δ-toc suppressed fat accumulation and hypertrophy of brown adipocytes in mice. We previously reported that α-toc and δ-toc intake significantly suppressed weight gain in these mice (Table S2) 10) . The results of this study suggest that the maintenance of thermogenesis and energy consumption in BAT is involved in the anti-obesity effect of α-toc and δ-toc ingestion.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In this study, the ingestion of α-toc and δ-toc suppressed fat accumulation and hypertrophy of brown adipocytes in mice. We previously reported that α-toc and δ-toc intake significantly suppressed weight gain in these mice (Table S2) 10) . The results of this study suggest that the maintenance of thermogenesis and energy consumption in BAT is involved in the anti-obesity effect of α-toc and δ-toc ingestion.…”
Section: Discussionmentioning
confidence: 76%
“…The breeding conditions for mice are the same as previously reported 10) . Male C57BL/6JJcl strain mice (three weeks old, n=25) were purchased from CLEA Japan, Inc. and housed individually in plastic cages in an environment controlled at 23℃±2℃ and 55%±5% humidity, with a 12 h light/dark cycle.…”
Section: Animals and Dietsmentioning
confidence: 99%
“…In addition to its antioxidant effects, α-tocopherol can signi cantly inhibit the gene expression of in ammatory cytokines IL-1β and IL-6 in adipocytes. Dietary supplementation with α-tocopherol reduces the expression of in ammatory factors such as leptin, IL-6, and TNF-α in adipose tissue of obese rats [31,32], suggesting bene cial effects of α-tocopherol in lowering levels of oxidative stress and antiin ammatory effects in adipose tissue. In the present study, α-tocopherol content in adipose tissue increased in ASED and OSED groups (Table 2 & Table 3), consistent with other ndings [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we would like to conduct a step-bystep examination of the anti-obesity and anti-inflammatory effects of food ingredients using this obesity-induced inflammation-induced mouse model. From two papers, we found that both vitamin E homologs (αand δ-tocopherols) 2) and sweet basil extraction 17) have anti-inflammatory effects on 3T3-L1 adipocyte-induced inflammation in vitro. Unfortunately, neither vitamin E homologs nor sweet basil powder showed anti-inflammatory effects on adipose tissue in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculated that vitamin E, especially αand δ-tocopherols might have antiinflammatory effects on adipose tissue. The experiment 2) was conducted using male C57BL/6JJcl strain mice. Initially, these mice were fed a basic diet for 1 week to allow them to adapt to the new environment.…”
Section: What Is Sweet Basil?mentioning
confidence: 99%